BASIC FEATURES OF LINGUISTIC CHARACTER OF THE WORD MEANING (American Journal of Research in Humanities and Social Sciences, 2023)
In this article, basic features of linguistic character of the word meaning are analysed. As well as, the article gives a complete description of the meaning of the word, its actualization, the role of context and cites example sentences.